2013
DOI: 10.4103/0976-237x.123022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different adhesion strategies on fiber post cementation: Push-out test and scanning electron microscopy analysis

Abstract: Aim:The aim of this study was to investigate the effect of phosphoric acid etching and the dentin pre-treatment with sodium hypochlorite (NaOCl) on the push-out bond strength between fiber post and root canal dentin.Materials and Methods:Root canals of 48 human incisors were selected, post spaces were prepared and assigned to four groups: G1-37% phosphoric acid (15 s); G2-5.25% NaOCl (2 min) +37% phosphoric acid (15 s); G3-37% phosphoric acid (60 s); and G4-5.25% NaOCl (2 min) +37% phosphoric acid (60 s). Fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…In the present study, no improvement in the BS was found for the groups treated with NaOCl, which is similar to the findings by Saraiva et al 20 and Lindblad et al 21 . Those studies also found no improvement in the results of adhesive BS in root canals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, no improvement in the BS was found for the groups treated with NaOCl, which is similar to the findings by Saraiva et al 20 and Lindblad et al 21 . Those studies also found no improvement in the results of adhesive BS in root canals.…”
Section: Discussionsupporting
confidence: 93%
“…In order to reduce intraradicular pin displacement failures and to prolong the longevity of teeth restored with this apparatus, studies are conducted to investigate the performance of different dental substrate treatments in order to obtain greater durability and efficacy of the adhesive interface [18][19][20] . Studies have investigated the action of CHX 19,[21][22][23] and NaOCl 24 on root dentin, in order to maintain the integrity of the hybrid layer.…”
Section: Introductionmentioning
confidence: 99%
“…The bond strength in the current study was investigated using a push-out testing method, which has been reported to apply a shear stress parallel to the FP and CC interface that is comparable to the clinical situation ( Bitter et al, 2007 , Saraiva et al, 2013 , Santos et al, 2017 ). Furthermore, the recorded push-out bond strength values revealed limited variability which indicated high reproducibility of the measurements using the push-out testing method ( Goracci et al, 2004 , Goracci et al, 2007 , Arslan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of the etching gel could bring about the persistence of an oxygen-rich layer in the post space apical dentin. However, the use of 37% of phosphoric acid for 60 s increased the bond strength in the apical third of the root dentin [ 69 ].…”
Section: Discussionmentioning
confidence: 99%